Adiposity and response to an obesity prevention intervention in Pakistani and Bangladeshi primary school boys and girls: a secondary analysis using the BEACHeS feasibility study. Issue 2 (9th February 2016) - Cezard, Geneviève; Bansal, Narinder; Bhopal, Raj; Pallan, Miranda; Gill, Paramjit; Barrett, Timothy; Adab, Peymane
Abstract : Objectives: As a secondary analysis of the BEACHeS study, we hypothesised there would be sex differences in Pakistani and Bangladeshi school children when examining adiposity and their response to an obesity intervention. Design: The Birmingham healthy Eating and Active lifestyle for CHildren Study (BEACHeS) was designed as a Phase II feasibility study of a complex intervention. Setting: 8 primary schools with predominantly South Asian children in Birmingham, UK Participants: 1090 pupils (aged 5–7 years old) from school year 1 and 2 were allocated at school level to receive an intervention. A total of 574 were enrolled in the study with consent. We focused on the 466 children of Pakistani and Bangladeshi origin (50.6% boys). Intervention: Delivered between 2007 and 2009, the 1-year obesity prevention intervention targeted school and family-based dietary and physical activities. Primary and secondary outcome measures and analysis: Adiposity measures including skinfold thickness were compared by sex at baseline and follow-up. Gains in adiposity measures were compared between control and intervention arms in boys and in girls. Measures were compared using two-sample t tests and Wilcoxon-Mann-Whitney rank sum tests according to normality distribution. Results: At baseline, girls had larger skinfold measures at all sites compared to boys although body mass index (BMI) was similar (eg, median subscapular skinfold 6.6 mm vs 5.7 mm; p<0.001). At follow-up, girls in the intervention group gained less weight and adiposity compared to respective controls (p<0.05 for weight, BMI, waist circumference, central and thigh skinfold) with a median total skinfold gain of 7.0 mm in the control group compared to 0.3 mm in the intervention group. Conclusions: Our secondary analysis suggests differences in adiposity in Pakistani and Bangladeshi girls and boys and in the effect of the intervention reducing adiposity in girls. These preliminary findings indicate that including sex differences should be examined in future trials. Trial registration number: ISRCTN51016370; Post-results.